Letter (copy) : International Solidarity Fund - Citrine, Walter, 1887-1983
030-0094-001 Secretary' s. WMC/HVT/FC/580. Mr. W. Schevenels, 10th August, 1938. The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Schevenels, INTERNATIONAL SOLIDARITY FUND. I am enclosing a further cheque for £3,000 for the International Solidarity Fund from monies raised in this country in the hope that it will assist in the continuance of the vital work which is being undertaken by the Fund. I shall be glad if you will let me have your official receipt for this amount. Yours sincerely, General Secretary. Cheque. 292/946/30/94